2021
DOI: 10.12688/wellcomeopenres.16745.1
|View full text |Cite
|
Sign up to set email alerts
|

Acquiescence and submission to COVID-19 vaccination: ethics considerations

Abstract: Compelling individuals to be vaccinated with candidate vaccines that have been granted emergency use approval based on limited data, and penalising non-compliance, raises challenging ethics issues. For instance, some individuals may wish to be vaccinated, but may be hesitant to be vaccinated with particular vaccine candidates. On the other hand, some individuals may be averse to vaccination of any sort but may find themselves being forced to submit to vaccination in certain situational contexts to gain access … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Funding such major networks inevitably involves opportunity costs—for other kinds of research, and for research institutions not involved in those networks. Here, and in the five WHO-commissioned reviews,2 9–12 we draw attention to how all parts of the research ecosystem need to keep in view these key ethical questions of power, equity and respect for local contexts and needs, as they take forward these effective models of research.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Funding such major networks inevitably involves opportunity costs—for other kinds of research, and for research institutions not involved in those networks. Here, and in the five WHO-commissioned reviews,2 9–12 we draw attention to how all parts of the research ecosystem need to keep in view these key ethical questions of power, equity and respect for local contexts and needs, as they take forward these effective models of research.…”
Section: Discussionmentioning
confidence: 99%
“…The success of adaptive platform trial designs in responding to COVID-19, and the endorsement by the WHA of major clinical trial networks, highlights the need to review experience to date so that trials can be conducted even quicker and better in future emergencies: driven by scientific rigour, and underpinned by sound ethical practice. Drawing on five reviews commissioned by the WHO Health Ethics and Governance Unit,2 9–12 that subsequently formed the basis for an expert round table held in Geneva in July 2022, we offer the following ethics-related key considerations to support the further development of international collaborative adaptive platform trials. Priority questions for future research and practice identified at the round table are set out in box 1.…”
Section: Looking To the Futurementioning
confidence: 99%
See 1 more Smart Citation